2022
DOI: 10.1177/23743735221125439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Engagement on Healthcare Quality: A Scoping Review

Abstract: Patient engagement (PE) is a well-known strategy introduced and implemented by pharmaceutical and medical device companies for patient compliance and adherence to treatment protocols during clinical trials and care processes. This can affect a wider range of outcomes such as the quality of treatment decisions and quality of care outcomes. Few studies have paid attention to it. The involvement of patient is one of the crucial stakeholders of health care in their treatment that makes controversial opinions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…More research into novel interventions that build on theoretical models is needed for successful health promotion in this area. Moreover, placing the patient at the forefront of decision making is important for improving health outcomes, reducing costs and enhancing the patient‐doctor relationship 26 . With such wide‐ranging benefits it is clear that finding ways of effectively engaging of patients in their treatment decisions is key.…”
Section: Discussionmentioning
confidence: 99%
“…More research into novel interventions that build on theoretical models is needed for successful health promotion in this area. Moreover, placing the patient at the forefront of decision making is important for improving health outcomes, reducing costs and enhancing the patient‐doctor relationship 26 . With such wide‐ranging benefits it is clear that finding ways of effectively engaging of patients in their treatment decisions is key.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, ePRO is expected to improve patient participation [ 23 ]. However, previous randomized controlled trials on ePRO have not evaluated the improvement of patient participation, which is an important mediator in regular clinic visits [ 4 , 13 , 15 , 18 , 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased participation has the potential to promote quality of care and invigorated self‐efficacy for patients 33 . However, previous studies have shown that ensuring patient participation in PHC nurses' daily practice can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…7,32 Increased participation has the potential to promote quality of care and invigorated self-efficacy for patients. 33 However, previous studies have shown that ensuring patient participation in PHC nurses' daily practice can be challenging. Therefore, more research on the conditions that can enable patient participation and the barriers that currently hinder it remains necessary.…”
Section: Introductionmentioning
confidence: 99%